Sertifikasi Phenyl: Persepsi Masyarakat dan Dampak Sertifikasi pada Pengusahaan Hutan Skala Lokal (Studi Kasus di Kelurahan Selopuro dan Desa Sumberejo, Kecamatan Batuwarno, Kabupaten Wonogiri, Propinsi Jawa Tengah) - Teguh Yuwono (Fakultas Kehutanan Universitas Gadjah Mada, 2008)
Phenyl Certification: Public Perception and Impacts of Certification of the Local Scale Forest Management (Study Case in Selopuro and Sumberejo Villages, Batuwarno Sub District, Wonogiri Regency, Central Java)In 2002, Indonesian Ecolabel Institution (LEI) established the so-called Sustainable Community Based Forest Management Certification system (PHBML). In 2004, with a PHBML certificate award, the community forest management units in Selopuro and Sumberejo villages, Batuwarno sub district, Wonogiri Regency, Central Java were anknowledged as the best institution in sustainable yield function, social function, and ecological function aspects. This research was aimed to find out the community's kind of perception, as well as that of KPS (Certification Farmer Community) officials and members in particular, to PHBML certification implementation. Also, the study was intended to discover the impact of PHBML certification upon the local scale forest management.The research findings indicated that the community's level of understanding to PHBML certification was poor when compared with that of KPS officials. This condition due to the official failure to share the knowledge they had receivedfrom NGO with the KPS members. With PHBML certification, the institutional management by forest farmers had been proven improved however, there have not been yet any significant improvement to farmer income, and to forest product marketing. In addition to this, what was meant by significance, did not fully answer the farmer expectation of better sustainable forest principle realization.